Recent advances in lyotropic liquid crystal nanoparticle formulations for drug delivery systems - Subash, Paranthaman; Khute, Sulekha (Frontiers in Soft Matter, 2025)
Lyotropic liquid crystalline (LLC) nanoparticles have gained significant attention as drug delivery systems owing to their unique self-assembly properties, biocompatibility, and ability to encapsulate both hydrophilic and hydrophobic drugs. This chapter explores recent advances in LLC formulations, focusing on their structural classification, physicochemical properties, and applications in controlled-drug delivery. Various mesophases, including lamellar, cubic, and hexagonal structures, have been discussed, highlighting their roles in controlled release. A comparative analysis reveals that cubic phases offer superior structural stability for sustained release, while hexagonal phases excel in high-viscosity applications, though their complex preparation limits scalability. In addition, key characterization techniques such as small-angle X-ray scattering, differential scanning calorimetry, and rheology are examined to offer insights into their stability and performance. Furthermore, the development of in situ gelling precursor systems and their applications in oral, transdermal, ocular, nasal, injectable, and periodontal drug delivery have been explored. The incorporation of stimuli-responsive materials into LLC systems enhances their adaptability to personalized medicine and advanced therapeutic strategies. Despite these advancements, challenges such as scalability, long-term stability, and clinical translation remain unresolved. This chapter highlights the potential of LLC nanoparticles to revolutionize modern drug delivery by improving bioavailability, therapeutic efficacy and patient compliance. Future research should focus on optimizing formulation strategies and exploring novel biomaterials to expand the clinical utility of LLC-based drug delivery systems.